Inside the academy and out: lesbian/gay/queer studies and social action - Ristock, Janice L.; Taylor, Catherine G. (University of Toronto Press, 1998)
Inside the Academy and Out demonstrates that the pedagogical and theoretical insights offered by lesbian/gay/queer studies can have relevance to a broader social sphere. The essayists represented here come from a wide range of disciplines, including English, education, philosophy, sociology, and women's studies. Their essays are divided into two broad areas: 'Pedagogy and Research' and 'Spheres of Action.' Taken together, they explore teaching and research theory, examining their implications in areas such as AIDS education, social services, law reform, and popular culture.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; droit; ethnographie; intersectionnalité; justice sociale; militance; premier cycle; pédagogie; périodes historiques; queer; santé; science politique et droit; sciences de l'éducation; sciences humaines; sexologie; soc2014; thématiques; violences

Kanehsatake 270 ans de résistance - Obomsawin, Alanis; Koenig, Wolf; Dionne, Claude; Teufel, Dagmar; Vallée, Jacques; Office national du film du Canada (Office national du film du Canada, 1993)
"Par une chaude journée de juillet 1990, une confrontation historique a propulsé les problèmes des Autochtones de Kanehsatake et du village d'Oka au Québec au premier plan de la scène internationale et de la conscience des Canadiens. Au cours de cet été épuisant, la productrice et réalisatrice Alanis Obomsawin, elle-même Indienne abénaquise, a passé 78 jours et nuits angoissants derrière les barricades dressées par les Mohawks, à tourner des images du conflit armé les opposant à la Sûreté du Québec et l'Armée canadienne."--Conteneur.
Keywords: 1900-1999; 1990-1999; Kanehsatake; amériques; approches et analyses; canada; cinéma; communication; cours; discipline; féminisme autochtone; justice sociale; militance; oka; premier cycle; premières nations; périodes historiques; québec; régions géographiques; résistance; sex2283; thématiques; violences

Les femmes autochtones et la justice pénale - Jaccoud, Mylène (Criminologie, 1992)
The interest in understanding and analyzing the situation of native women within the penal process is recent and seems to be limited by the inordinate attention paid by researchers to the overrepresentation of native women. This article is an account of the findings and analyses made to date in this recent sector of research. It presents an inventory of the principal data concerning the confrontation of native women with the penal process. It proposes a synthesis of the principal analyses of the problems of native women with the system of justice by presenting a critical analysis of the socio-structural model of LaPrairie.
Keywords: amériques; approches et analyses; canada; cours; criminologie; discipline; droit; droits des femmes*; droits des femmes* autochtones; histoire et politique; intersectionnalité; justice sociale; pol4105; premier cycle; racisme; régions géographiques; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences